PENCIPTAAN ARTISTIK DENGAN PENDEKATAN REALISME MAGIS DALAM FILM PENDEK “PANTAI INI MILIK SIAPA?” DI CV. RADITYA JAYA MAHARDIKA - Glorya Trivika; I Kadek Puriartha; Putu Raditya Pandet (CALACCITRA: JURNAL FILM DAN TELEVISI, 2026)
Film is an audio-visual medium that serves not only as entertainment but also as a means of conveying ideas and social reflection through aesthetic expression. Artistic elements play an important role in shaping atmosphere, strengthening character portrayal, and supporting narrative meaning. This Final Project report discusses the creation of the short film “Pantai Ini Milik Siapa?”, focusing on the role of artistic elements in supporting a magical realism approach. The study emphasizes the use of makeup and visual design as symbolic visual strategies to represent social issues. The results show that conceptually designed artistic elements effectively support magical realism while reinforcing character development and social commentary.